2012
DOI: 10.4081/jlimnol.2012.e8
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton functional traits and seston stable isotopes signature: a functional-based approach in a deep, subalpine lake, Lake Maggiore (N. Italy)

Abstract: The seasonal variation of seston stable isotopes signature of carbon (δ13C) in Lake Maggiore during 2008 was related to seasonal variation of the lake phytoplankton community, investigated in terms of phytoplankton taxonomic groups, morpho-functional groups (MBFG), cell size classes and cell shape classes. Three open water stations were selected to reflect truly pelagic, influenced by littoral and riverine carbon sources; phytoplankton samples were collected from two water depths, 0-20 m and 25-50 m. Among sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 38 publications
(58 reference statements)
2
33
0
2
Order By: Relevance
“…In Lake Maggiore, Bacillariophycee are the most dominant phytoplankton group with a high biomass throughout the year [37,40]. In the year of our study (2009), a peak in the Bacillariophycee biomass of Aulacoseira sp., Asterionella sp., and Fragilaria sp.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In Lake Maggiore, Bacillariophycee are the most dominant phytoplankton group with a high biomass throughout the year [37,40]. In the year of our study (2009), a peak in the Bacillariophycee biomass of Aulacoseira sp., Asterionella sp., and Fragilaria sp.…”
Section: Discussionmentioning
confidence: 87%
“…Seasonal changes in the littoral and pelagic δ 13 C isotopic baseline were identified by a temporal shift towards less 13 C-depleted values in the summer, which is a trend commonly observed in thermally-stratified lakes [35,36]. In lacustrine systems, δ 13 C and δ 15 N of suspended particulate matter (seston) varies seasonally [37] because of differences in the allochthonous input, phytoplankton species composition, and primary productivity [38,39]. In Lake Maggiore, it has been demonstrated that δ 13 C of the primary consumer Daphnia longispina galeata gr.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N values of primary producers and primary consumers have been reported during periods of stratification in temperate lakes, but to our knowledge not in tropical lakes (Quay et al, 1986;Zohary et al, 1994;Hodell & Schelske 1998;Caroni et al, 2012). In addition, larger consumers such as fish have long tissue turnover rates (months to years, Hesslein et al, 1993) and thus are their isotopic signatures representative of their diet for longer periods of time (Post, 2002).…”
mentioning
confidence: 99%